What is a book review? The case of economics - Julien Gradoz (Duke University, Center for the History of Political Economy (CHOPE), 2025)
This article identifies the two approaches to defining a book review. The first defines a book review as a text published in the 'Book Reviews' section of a journal. The second approach involves specifying criteria that a text must satisfy to qualify as a book review and assessing whether a given text satisfies these criteria. This second approach reveals a significant overlap between book reviews and other types of publications in economics, such as encyclopedia entries, prefaces, review essays, and review articles.
Keywords: B20; Y30; 330; book reviews; economics journals; classification; publications; editors; review essays